Selênio e silício como amenizadores da toxicidade do cádmio em plantas de Pfaffia glomerata(Spreng.) Pedersen - Pereira, Aline Soares (2016)
The soil contamination with heavy metals such as cadmium ( causes damage to many plants . Among the alternatives sought to solve the problems with this toxic metal s in the growth of plants is the use of alleviators, ie elements considered beneficial , that when used in low concentrations may alleviate the damaging effects of toxic elements. In this sense, the present study aimed to evaluate the capacity of selenium (Se) and silicon (Si) to reduce the absorption and Cd toxicity in P faffia glomerata plants in hydroponic system . The P. glomerata plants were propagated in vitro and after acclimation transferred to hydroponic nutrient solution , where were added the follow ing combinations of Se (0 to 2.5 mM), Si (0 and 2.5 mM) and Cd (0 and 50 µ M) (T1: 0 µ M Cd + 0 mM Se and Si, T2: 0 µM Cd + 2 5 mM Se; T3: 0 µM Cd + 2 5 mM Si; T4: 50 µM Cd; T5: 50 µM Cd + 2 5 mM Se, T6: 50 µM Cd + 2 5 mM Si Data were submitted to analysis of variance and means were compared by the Scott Knott test at 5% probability of error. After exposure to different treatments (14 days)days), the plants were collected and analyzed for morphophysiological (fresh and dry weight, plant height, length and densit y of roots, leaf area, leaves number and photosynthetic parameters) and biochemical parameters (antioxidant enzymes, photosynthetic pigments content, hydrogen peroxide content, and damage to membrane lipids). The presence of Cd in nutrient solution promote d reduction in leaf area, biomass , morphological parameters of the root system and photosynthetic parameters, except for the shoot dry weight, leaf number and plant height. In general, in the treatments containing Se or Si with Cd, plants showed positive r esponses to the fresh weight of shoot and root s , root dry weight, length, diameter, volume and branching roots, leaf area, photosynthetic rate, internal CO 2 concentration, transpiration rate, water use efficiency and carboxylation of rubisco efficiency, th us showing that they can alleviate the Cd toxicity. The potential of Se and Si to ameliorate the Cd toxicity can also be seen in the contents of chlorophylls, carotenoids and H 2 O 2 , and in the superoxide dismutase (SOD) and guaiacol peroxidase (POD) activit y. F or lipid peroxidation Si was more effective than Se in ameliorate the Cd toxicity. Thus, t he potential o f the Si and Se to ameliorate the Cd toxicity can be used to increase the productivity and quality of medicinal plants in an environmentally proper manner